QLattes: An Open-Source Tool for Qualis Annotation and Visualization in the Lattes Platform - Mendonça, Nabor C.; Rodrigues, Maria Andréia F.; Mendonça, Lucas R. (Anais do Seminário Integrado de Software e Hardware (SEMISH); 2023: Anais do L Seminário Integrado de Software e HardwareDO - 10.5753/semish.2023.229845, 2023)
QLattes is an open-source browser extension for Chrome and Firefox that automatically classifies and annotates journal publications in CNPq’s Lattes Platform according to their Qualis categories. It also provides filtering, analysis, and visualization of Qualis-classified publication data extracted from Lattes CVs based on multiple metrics and perspectives. This paper presents a comprehensive description of QLattes, covering its user interface, architecture, implementation decisions, Qualis data sources, and performance. Additionally, the paper provides some preliminary data on the usage and impact of QLattes within the Brazilian academic community. The source code of QLattes is freely available at https://github.com/nabormendonca/qlattes .